2017
DOI: 10.2147/cia.s135030
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression levels of the insulin-like growth factor family in patients with AMD before and after ranibizumab intravitreal injections

Abstract: PurposeThe present study focused on the assessment of the mRNA levels of the insulin-like growth factor (IGF) family in patients with the exudative form of age-related macular degeneration (AMD) before and after ranibizumab intravitreal injections.Patients and methodsAn analysis of the expression profile of the IGF family of genes in patients with AMD was carried out using the oligonucleotide microarray and quantitative reverse transcriptase polymerase chain reaction (RT-qPCR) methods.ResultsIn the peripheral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 66 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…[27] Barbara et al reported significantly decreased expression of IGF2 mRNA in AMD patients after intravitreal injections of ranibizumab. [28] However, there is no literature on the methylation of these top 5 hypomethylation-high expression genes in relation with AMD. Here, we further investigated the methylation statuses of PIK3R1 , EZR , IGF2 , SLC2A1 , and CDKN1C in AMD patients’ blood samples.…”
Section: Discussionmentioning
confidence: 99%
“…[27] Barbara et al reported significantly decreased expression of IGF2 mRNA in AMD patients after intravitreal injections of ranibizumab. [28] However, there is no literature on the methylation of these top 5 hypomethylation-high expression genes in relation with AMD. Here, we further investigated the methylation statuses of PIK3R1 , EZR , IGF2 , SLC2A1 , and CDKN1C in AMD patients’ blood samples.…”
Section: Discussionmentioning
confidence: 99%